Magnetic Soils Profiles in the Volga-Kama Forest-Steppe Region - L.A. Fattakhova; A.A. Shinkarev; L.R. Kosareva (Учёные записки Казанского университета: Серия Естественные науки)
The magnetic properties of virgin forest-steppe soils developed on the originally vertically uniform unconsolidated parent material have been investigated. The profile samples of virgin dark-grey forest light-clayey soil derived from a siltstone of the Kazan layer of the Upper Permian and virgin leached medium-thick fertile light-clayey chernozem derived from a Quaternary heavy deluvial loam have been considered. Both soils are characterized by the accumulative type of magnetic susceptibility and F-factor values distribution patterns with depth. In the humus part of the soil profile, magnetics are present pre-dominantly in the < 2.5 µm fraction. The coercivity spectra allowed to determine the contribution of dia-/paramagnetic and ferromagnetic components to magnetic susceptibility. It has been found that magnetic susceptibility enhancement in the organogenic horizons of virgin forest-steppe soils occurs due to the contribution of ferromagnetic components. The results indicate a strong positive linear correlation between the magnetic susceptibility and oxalate-extractable Fe, as well as between the magnetic susceptibility and Schwertmann’s criterion values. Using the method of thermomagnetic analysis of the < 2.5 µm fraction, it has been found that the magnetic susceptibility enhancement in the profiles of forest-steppe soils took place due to the formation of maghemite-magnetite associations. The predominantly ferromagnetic fraction consists of small single-domain grains.